The Role Of 'Aisyiyah City of Tasikmalaya in Social Services, Education and Community Health - Sunanih Sunanih; Budi Hendrawan; Sharah Febrian (NATURALISTIC : Jurnal Kajian Penelitian Pendidikan dan Pembelajaran, 2022)
The development of 'Aisyiyah as a Muhammadiyah women's organization in West Java, especially Tasikmalaya, cannot be separated from the efforts and active role of the missionary since its inception in 1935 until now as Ahmad Dahlan hopes in encouraging women to pursue education, both in general and religious formal education. The struggle and movement of 'Aisyiyah are continuously carried out to benefit the community. This is due to the many problems faced by women and their families in various aspects of life. Asyiyah activities can be classified as community social service activities. The 'Aisyiyah movement in social services does not view 'money' as a goal, but rather gives benefits and wants to get the pleasure of Allah SWT. According to Suparlan, "Service is an effort to provide assistance or assistance to other people, both material and non-material so that other people can solve their problems" (Suparlan, 1983). The purpose of this study is to find out, in general, the role that has been felt by the community regarding the activities that have been carried out by 'Aisyiyah in the City of Tasikmalaya to help the community in social services and the specific purpose of knowing the role of 'Aisyiyah in the City of Tasikmalaya in social services in the fields of education and public health. The method of this research is a descriptive quantitative method of survey type.